Arquitetura e level design nos games - Casarini, Marcel (2014)
With virtual spaces becoming increasingly present in our daily lives, it is necessary to further understand the relationship that man to possess with this virtual space, as he understands it and how he can build it. As the massive use of games, these will be the object of analysis, since much of the virtual experience occurs in them. This research sought to establish the relationship between the factual and digital spaces in games in order to benefit the development levels of the game from the knowledge developed in architectural studies. The research is based on the thoughts of Mark Vitruvius, Martin Heidegger, Umberto Eco, Grant Hildebrand, Ernst Gombrich, Luís Carlos Petry, Nelson Brissac Peixoto and Lev Manovich, among others. The hypothesis of this study is that despite the differences between the factual and the virtual space, both can use the same concepts and methodology to be created, since they can also inhabited and are perceived similarly. Thus, in the first chapter of the research we tried to present a mimesis of the three-dimensional world in various media: painting, technical drawing and film, since they contributed to the understanding of the representation of virtual spaces. In the second chapter, we worked the relations of space for it actants with these environments and the relationship between user-architectural, who inhabits the factual space and the viewer-interactor, who inhabit the virtual environment, in addition to the concepts of navigable spaces, immersion and avatar, all important for reading the digital space and the development of their relationship to the factual space. Finally, in the third chapter, we performed a case study of the game "The Last of Us" from architectural concepts and design level and in relation to conceptual and methodological development part. Soon after, it was discussed directly the relationship between architecture and level design, and this time with the focus on the form of the creation of spaces, and how this is understood by the person who inhabits it. In the last part of the paper discussed the concept of architectural level design, which presents some ways of thinking about architecture and its relationship with the level design. From this conceptualization, we propose a development methodology architecture design level